Diffusion-weighted imaging and apparent diffusion coefficient values for evaluating terminal ileitis in patients with Crohn’s disease - Durayski,Evandra (2019)
Abstract Objective: To determine the accuracy of diffusion-weighted imaging (DWI) in identifying terminal ileitis in patients with Crohn’s disease. Materials and Methods: This was a retrospective study of 38 consecutive patients with Crohn’s disease who underwent magnetic resonance enterography with DWI in a 3.0 T scanner. The patients were divided into two groups, on the basis of colonoscopy and biopsy findings: active inflammation; and inactive disease. Apparent diffusion coefficient (ADC) values were determined, as were the magnetic resonance index of activity (MaRIA) and the Clermont score. Results: Of the 38 patients evaluated, 18 (47%) had active inflammation. The patients with active inflammation showed greater restricted diffusion, more pronounced mucosal edema, greater wall thickening, a higher MaRIA, and a higher Clermont score than did those with inactive disease. The level of interobserver agreement (intraclass correlation coefficient) was excellent for the MaRIA and the Clermont score, whereas it was substantial for the ADC values. For identifying colonoscopy-proven inflammation, the best ADC cut-off point was 2.1 × 10−3 mm2/s, which had a sensitivity of 88.8% and a specificity of 95.0%, whereas DWI presented an overall accuracy of 89.4%, with a sensitivity of 88.9% and a specificity of 90.0%. Conclusion: Visual analysis of the DWI sequence has good accuracy in detecting terminal ileitis in patients with Crohn’s disease. In addition, low ADC values have good sensitivity for detecting colonoscopy-proven inflammation.